Participação de antígenos do Schistosoma mansoni na indução de imunidade protetora e na modulação da reação granulomatosa - Cristine Hirsch Monteiro (1997)
To identify components of the egg and adult worm Schistosoma mansoni involved in the induction of protective immunity and modulation of granulomatous reaction to eggs, we employ techniques of fractionation and purification from soluble antigen extracts of these stages of the parasite. Components of soluble egg antigen preparation (SEA) of S. mansoni recognized by human monoclonal antibodies (AcMH) from schistosomiasis chronic intestinal patients (PCI) were obtained in affinity chromatography and were biochemically characterized with respect to molecular weight and the ability of these fractions to induce protection. Anionic fractions obtained from soluble antigen adult worm preparation(SWAP) of S martsoni were obtained from anion exchange chromatography using Q-Sepharose column attached to the FPLC system. The humoral and cellular immune reactivity induced by this Ag/fractions against serum and human cells and experimental animals was evaluated in ELISA assays, cell proliferation and granuloma formation in vitro. Due to its in vitro reactivity with peripheral blood mononuclear cells (MNSP) from schistosomiasis patients chronic intestinal (PCI), the PIII fraction, among other fractions of SWAP, was selected to be used in experiments to induce protection and modulation the in vivo granulomatous reaction. BALB/c and C57bl/6 mice were immunized with purified Ag from SEA using AcMH or PIII from SWAP. In both cases, we obtained significant degrees of protection, close to 50%, as measured by recovery of adult worms in portal system. The granulomatous reaction of animals immunized with PIII was compared for the area of the granuloma. Finally, there was the scanning of clones encoding recombinant proteins in cDNA library of the adult worm S. mansoni, reactive rabbit serum immunized with PIII, seeking to identify the antigenic components present in this fraction.